ENHANCING THE SELF-CONFIDENCE OF YPMAK-SPONSORED STUDENTS IN JAYAPURA THROUGH PUBLIC SPEAKING TRAINING - Sheilla Putri Agustin; Rizka Cintya Edwar; Leon Mitra Harju; Palti Maretto Caesar Manalu (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Public speaking is an essential competency for university students as it supports both academic achievement and future professional development. However, some students supported by Yayasan Pemberdayaan Masyarakat Amungme dan Kamoro (YPMAK) still experience difficulties in expressing their ideas confidently in front of an audience. The activity applied a participatory training approach that combined lectures, practical speaking exercises, and evaluation following each practice session. The training was conducted in December 2025 at the Management Laboratory of the Faculty of Economics and Business, Universitas Cenderawasih, involving YPMAK-assisted students as participants. The effectiveness of the program was assessed through pre-tests, post-tests, and direct observation of participants’ performance during speaking practice sessions. The results indicate an improvement in participants’ understanding of fundamental public speaking techniques as well as a noticeable increase in their confidence when presenting ideas in front of an audience. Overall, the program contributes to strengthening the communication competencies of the participating students.